Makna Konsep Kelahiran Kembali Menjadi Manusia Baru Berdasarkan Kolose 3:5-10 - Sebayanti Gamerakai; Malik Bambangan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Colossians 3:5-10 is a verse that describes the life of a new human person who has adapted and accepted Christ as Lord and loves himself. Based on Paul's opinion to the Colossian congregation, when the Colossian congregation became new people, they had to put away all their old lives, namely living in sin. But there are still those who have not fully lived in the new life. Likewise, the life of mankind, when they have been reborn into new humans, has not completely evolved from the old life. Still committing sins and old habits like humans live in modern times which always prioritize physical, visible, temporary and popular things. On the other hand, Christians also ignore the true self, the spiritual self, the invisible, the eternal and the hidden. By writing this article, the aim is to invite and encourage Christians to adapt seriously and live in holiness that is continually renewed in the image of God's Creator. The method used by the author is a literature research study method using book sources.